2009
DOI: 10.1126/science.1162986
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time DNA Sequencing from Single Polymerase Molecules

Abstract: We report here on the genome sequence of Pasteurella multocida Razi 0002 of avian origin, isolated in Iran. The genome has a size of 2,289,036 bp, a GC content of 40.3%, and is predicted to contain 2,079 coding sequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
2,449
0
33

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 3,222 publications
(2,545 citation statements)
references
References 37 publications
5
2,449
0
33
Order By: Relevance
“…The principles behind these four systems are schematically depicted in Figure 3. Additional platforms exist, such as the Polonator[62], the Helicos Single Molecule Sequencer[63], and an in-house only nanoarray-based sequencing-by-ligation technology developed by Complete Genomics[64]. These latter systems remain quite limited in their use and will not be discussed.…”
Section: Massively Parallel Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…The principles behind these four systems are schematically depicted in Figure 3. Additional platforms exist, such as the Polonator[62], the Helicos Single Molecule Sequencer[63], and an in-house only nanoarray-based sequencing-by-ligation technology developed by Complete Genomics[64]. These latter systems remain quite limited in their use and will not be discussed.…”
Section: Massively Parallel Sequencingmentioning
confidence: 99%
“…Pacific Biosciences’ PacBio RS detects fluorescently labeled nucleotides in real time as they are incorporated during a second-strand synthesis (Fig. 3)[63, 120]. Oxford Nanopore’s sequencing platform uses an exonuclease cleavage reaction and a protein nanopore to sequence individual cleaved bases by a unique electrical signature as they are transported through the pore[121].…”
Section: Future Prospectsmentioning
confidence: 99%
“…However, to improve accuracy in such endeavors, there is a need for genomic resources with far more contiguous sequence and less pervasive gaps. The acquisition of such contiguous sequences is possible now with third generation sequencing technologies, such as Single Molecule Real Time (SMRT) sequencing technology [Eid et al, 2009], which provide mean read lengths that are more than an order of magnitude larger than earlier sequencing technologies. The reads can span repetitive elements, resulting in longer contigs and minimal gaps within scaffolds [Bickhart et al, 2017], [Jiao et al, 2017], [Gordon et al, 2016].…”
Section: Introductionmentioning
confidence: 99%
“…Determination of DNA sequences from a single DNA can result in an ultra-high-throughput sequencing of DNA or RNA without any amplification, thus reducing cost and increasing accuracy compared to the conventional Sanger sequencing techniques. Recently these optical (Eid et al, 2009) or electrochemical (Rothberg et al, 2011) methods for singlemolecule DNA sequencing have been commercialized. Furthermore, Zong et al (2012) identified single-nucleotide and copy-number variations via sequencing single cell genome without error-prone exponential amplification.…”
Section: Dna Sequencingmentioning
confidence: 99%